How Light Affects Child’s Visual Perception In Educational Spaces? - Fercha, Nessma; Benbouaziz, Akila (Journal of Architecture and environment of child, 2022)
The interaction between lighting design within an architectural space and a child's visual perception is significant, yet it remains largely unnoticed or even ignored, especially within educational buildings. Moreover, this relationship goes beyond simply ensuring the function of vision and perception of the surrounding environment, as many studies have proven that any defect or difficulties in providing appropriate and necessary lighting conditions affect the visual responses to light, and thus on the visual perception of students, as that the latter is an important factor in child’s academic performance And his motor skills development, especially in the educational environment. The inadequacy of this environment for the child's visual needs results in visual problems that negatively affect the child's ability to read and learn, and consequently, school failure. This paper endeavors to create an understanding of how the use of lighting conditions affects children's visual perception in the classroom. The research follows in achieving its objective and proving its hypothesis on the descriptive analytical approach to study the research problem. And based on the results and conclusions of the study, The study recommended that attention should be paid to light’s characteristics in the design of educational buildings to provide a good quality of the educational environment for its role in the success of the child's visual perception process and to avoid problems that impede his healthy development.